Applying GRADE in systematic reviews of complex interventions: Challenges and considerations for a new guidance - Movsisyan, A (2018)
Background: The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach offers a transparent framework for rating the certainty of evidence in systematic reviews. Concerns, however, have been raised that use of GRADE beyond biomedical interventions frequently downgrades the “best evidence possible” for many complex interventions. This DPhil thesis aims to (1) further investigate the challenges of using GRADE in systematic reviews of complex interventions, (2) explore how the GRADE approach can be advanced to address these challenges, and (3) inform the write-up and dissemination of a new GRADE guidance for complex interventions. Methods: To address the broad aims of this thesis a range of methodological approaches were employed, primarily drawing on the best-practice techniques for developing research reporting guidelines (see Chapter 2). First, a systematic literature review method was used to establish whether an adequate system already exists for rating the certainty of evidence for complex interventions and informing the need for a new guidance (Chapter 3). Further consultation with experts, including semi-structured interviews with review authors and GRADE methodologists, provided a nuanced understanding of the challenges of applying GRADE in reviews of complex interventions and suggestions for advancing the guidance on GRADE (Chapter 4). Agreement around these suggestions was explored in a Delphi-based online expert panel (Chapter 5), and the content of the new GRADE guidance for complex interventions was discussed indepth in a three-day expert meeting held in Oxford in May 2017 (Chapter 6). Results: The systematic literature review identified a few systems attempting to modify GRADE for public health interventions; however, there was little reporting of rigorous procedures in the development and dissemination of these systems. Qualitative interviews captured differences in views on GRADE use between review authors and GRADE methodologists. Specifically, GRADE methodologists found it critical to consider GRADE from the beginning of the review process and exercise judgment in GRADE ratings. Review authors, on the other hand, often thought of GRADE as an “annoying add-on” at the end of the review process and felt challenged by the need to be more interpretative with evidence and sift through many publications on GRADE. Suggestions were made to enhance the GRADE guidance. No significant disagreement was found in the online expert panel on any domain of evidence, and the expert meeting provided further insights into the content of the new GRADE guidance for complex interventions. Participants agreed that the new guidance should specify the meaning of the construct of “certainty of evidence” for complex interventions, consider revisions of the initial categorisation of evidence based on study design, and better assess the coherence of the causal pathway of complex interventions. Conclusion: This thesis work consolidates up-to-date methodological knowledge on reviewing complex interventions by providing critical examination of the existing approaches and new insights. In transparent reporting of the research phases, it informs development of a new GRADE guidance on rating the certainty of evidence in systematic reviews of complex interventions.